Water Supply in a War Zone : A Preliminary Analysis of Two Urban Water Tanker Supply Systems in the Republic of Yemen - Abu-Lohom, Naif Mohammed; Konishi, Yasuo; Mumssen, Yogita; Zabara, Bilkis; Moore, Scott Michael (World Bank, Washington, DC, 2018)
A combination of poverty, water scarcity, armed conflict, and warfare has produced serious challenges for both water supply and sanitation in Yemen. Although the tanker truck system plays a critical role in filling this gap, it raises serious questions with respect to affordability, health, environment, and water resources management. Because active conflict makes parts of the country remain inaccessible, little recent data are available on the state of the country’s water supply and sanitation systems. This discussion paper presents assessments of basic features of urban water supply systems in Sana’a and Aden, a detailed profile of the tanker truck service structure, including supply chain mapping, value chain analysis, and an assessment of changes to the sector since the war began. It also covers institutional support structure for the water sector, well-to-consumer supply chain, water quality, well operations, tanker trucks water delivery services, and household water demand. The analysis culminates in recommendations of interventions urgently needed to improve service delivery in Yemen’s two largest cities.